Outcomes following the excision of sarcoma and chest wall reconstruction using 3D printed implant - Lei Wang; Xiaolong Yan; Jing Li; Jinbo Zhao; Jian Wang; Sanhu Yang; Dichen Li; Changquan Shi; Shaomin Li; Junqi Wang; Tao Jiang; Lijun Huang (iScience, 2024)
Summary: The survival outcomes of patients with chest wall sarcomas (CWS) were evaluated after receiving wide excision and chest wall reconstruction by using three-dimensional printed (3DP) implants. The survival outcomes evaluating the effect of 3DP implants for chest wall reconstruction is lacking. Here, forty-nine patients with CWS underwent radical wide excision and chest wall reconstruction using 3DP implants. The surgical data and long-term survival outcomes were collected and analyzed. With a median follow-up of 36 months, the disease-free survival (DFS) and overall survival (OS) were 31.7% and 58.5%, respectively. In addition, the 3-year DFS and OS can be significantly differentiated using the classification criteria of tumor grade, tumor size tumor area. Hence, wide excision and chest wall reconstruction using three-dimensional printed implants are a safe and effective treatment for chest wall sarcoma. The novel classification criteria of tumor size and area have the potential to predict the prognosis of CWS.